Strategi Social Media Marketing dalam Membangun Kompetensi Berwirausaha Siswa SMK - Nanda Andreas Octavini; Maulina Agustin; Sevi Andriasari; Iis Ariska Nurhasanah; Levina Rachmawati Putri (PT. Karya Inovatif Nusantara, 2026)
The development of digital technology requires vocational high school students to possess entrepreneurial competencies that can adapt to modern marketing changes. However, the use of social media as a digital promotion tool is still not optimal, particularly in managing marketing content and business social media accounts. This community service activity aimed to improve students’ understanding and skills in utilizing social media as a business promotion medium. The program was implemented through training and practice-based mentoring (project-based learning), including material presentation, creation of business social media accounts, development of promotional content, use of hashtags, and consumer interaction strategies. The results showed that participants were able to independently create business social media accounts and understand the basic strategies of social media marketing to support product promotion. In addition to improving technical skills, this activity also increased participants’ motivation and confidence in developing digital-based businesses. Therefore, this program is expected to support the improvement of vocational students’ digital entrepreneurial competencies in facing business development in the digital era.